A review of online trust branding strategies of financial services industries in Malaysia and Australia - Teck Ming Tan; Devinaga Rasiah (Advances in Management & Applied Economics, 2011)
This study spotlighted on the financial services industry specifically in the creation of brand trust across online channel, which constructs a significant contribution to the under-researched area of online branding. Content analysis was performed on the web sites of top ten bank retailers in Malaysia and Australia. An analysis of the extent to which the retailers were using their web sites to provide online financial services and brand information provided a context for a more detailed analysis of online trust branding strategies, including communicating brand trust and value, and building brand experience relationships via online financial services. Bank retailers in Australia provided guarantee statements and variety of financial services across online channel, offering comprehensive online strategy for brand trust and brand experience. There was indication of some innovative practice, but also scope for substantial further improvement of the concept of online trust branding. Conversely the bank retailers in Malaysia only provided basic online financial services and no guarantee of refund for any financial fraud cases. Their use of the online channel to communicate brand trust, brand value, and to endorse brand relationships was underdeveloped.
Keywords: G2; M31; M37; L86; 330; brand trust; online branding; financial services industry; online banking